RETRACTED: Nexus Between Equity Pricing Models and Equity Price Fragility: Empirical Insights From Pakistan - Anser, Muhammad Khalid; Yusop, Zulkornain; Abbas, Shujaat; Ali, Sajid; Ahmad, Munir (Frontiers in Energy Research, 2022)
Purpose: The study tests conventional and behavioral pricing multifactor impact on price fragility from the equity market of Pakistan. Methodology: The positivist approach is used to deduct study rationale via probability sampling. While, systematic sampling for data collection of PSX and have tested sample in parallel to mean variance random walk theory. Findings: The impact of conventional factors is significant on price fragility in short run and vice versa in long run. Specifically, herd behavior and disposition effects are found insignificant. But Size, value, illiquidity, price earning resulted significant impact on price fragility in short run. Limitations: Recent research has not covered desired scope of researcher due to time limitation i-e Lack of harmony is in corporate data on databases; literature of price fragility is very scarce Implication: In PSX there is big need to develop corporate culture to promote standard modern financial practice to enhance financial productivity and sustainability. For corporate culture sound corporate governance boards should be established, family governance system should be replaced by independent democratic board. Mispricing and arbitragers need serious control. Originality: The value of the research is in framework that has very scarce research about pricing multifactor impact on price fragility in entire universe.